Defining the Core Proteome of the Chloroplast Envelope Membranes - Simm, Stefan; Papasotiriou, Dimitri; Ibrahim, Mohamed; Leisegang, Matthias; Müller, Bernd; Schorge, Tobias; Karas, Michael; Mirus, Oliver; Sommer, Maik; Schleiff, Enrico (Frontiers in Plant Science, 2013)
High-throughput protein localization studies require multiple strategies. Mass spectrometric analysis of cellular fractions is one of the complementary approaches to a diverse array of cell biological methods. In recent years, the protein content of different cellular compartments and subcompartments was approached. Despite of all the efforts in this direction, analyzing membrane fractions is still a difficult task, as e.g. the dissection of the proteome of the envelope membranes of chloroplasts or mitochondria is often not reliable, since sample purity is not always warranted. Moreover, proteomic studies are often restricted to single (model) species, and therefore limited in respect to differential individual evolution. In the study at hand, we have dissected the different chloroplast subcompartments from the model plant Pisum sativum to determine the protein content in the inner and outer envelope membrane. Additionally, we have analyzed the proteome of the mixed envelope membranes of Arabidopsis thaliana and Medicago sativa for inter-species comparison. Further the protein content in the stroma and thylakoid of A. thaliana has been used as a control pool. The analysis yielded a total of 825 proteins in the various fractions isolated. In our study 157 of them were exclusively found in envelopes. The general overlap of our results with previous studies was limited to 38 sequences. Based on this, we provide a detailed map of the outer and inner envelope proteome. We conclude (i) that several alternative sample purification techniques and analysis strategies have to be combined to justify conclusions based on proteomics alone, and (ii) that generalization of results requires the comparison of different species and developmental states.